Studies On The Effect Of Benzo(a)Pyrene In Rats - Thoria, Ali Abdul Hameed Dragh (2001)
Benzo(a)pyrene [B(a)P] is a carcinogen found in high concentrations during the Malaysian haze episodes. In view of developing strategies in alleviating deleterious effects of haze in humans, the effect of acute and chronic exposure to B(a)P was studied in rats. In the acute exposure studies, an evaluation of apoptosis following treatment with B(a)P was assessed. The B(a)P treated rats received 24 ng (l3uL) of B(a)P instilled intratracheally, while similar volumes of trieaprylin (Tr) was administered to rats from the Tr group. Rats not receiving any treatment served as controls. An assessment of apoptosis was made on haematoxyl in and eosin (H&E) stained histologic sections, terminal deoxynuclcotidal transferase-mediated dUTP-biotin nick end labeling (TUNEL) analysis and DNA laddering of lung samples. Rats in the B(a)P group were killed at 1, 2, 4, 8, 16, and 24 hours post-instillation (p.i.) and rats from the control and Tr groups were only killed 24 hours p.i. Apoptos is at different stages was found in the pneumocytc and bronchial epithelium of B(a)P-treated rats killed 8, 16 and 24 hours p.i. This was also confirmed positive by TUNEL analysis and DNA laddering. In the chronic exposure studies, changes in the lung of D(a)P-induced rats during a three month period encompassing p53 expression, proliferating cell nuclear antigen (rCNA) expression, immune response (IgA, IgGl evels and alveolar macrophage activity), levels of glutathiolls-transferase (GST) marker enzyme and the effect of raw garlic as an anti-tumour agent were studied. Rats from the control, B(a)P and Tr group were daily fed on a commercial basal diet while rats from the garlic (G) and [B(a)P+GJ group were fed the basal ration containing garlic incorporated at the rate equivalent to an intake of 80m g/kg bodyweight/rat/day. The results showed growth disturbances in pneumocytes and bronchial epithelium of rats from the B(a)P group. Apoptosis was detected in four rats from the B(a)p-lG group. The PCNA positive areas were only found in hyperplastic areas in the lungs of rats from the B(a)P-treated group. In addition, rats treated with B(a)P and B(a)P+G had lower levels of IgA, IgG, alveolar macrophages activities and glutathione S-transferase in the lung. In conclusion, either short or long term exposures to B(a)P produce detrimental changes to lungs of rats and garlic has great potential in alleviating the chronic effects.